Exploring Fluidization Dynamics and Chemical Performance in Silicon Tetrachloride (SiCl4) Hydrochlorination Processes within a Fluidized Bed Reactor: Development and Analysis of an Eulerian-Granular Model - Rasheed, Ekehwanh; Saleh, Saad Nahi; Humadi, Jasim (Communications in Science and Technology, 2025)
The present work examines the complex fluidization pattern and reactive interactions of silicon tetrachloride (SiCl4) during hydrochlorination in a fluidized-bed reactor (FBR), a system that remains difficult to model accurately. To address this gap, we develop a new Eulerian–granular CFD framework that for the first time couples the Eulerian–Eulerian fluid model with KTGF specifically for SiCl4 hydrochlorination, enabling prediction capabilities that are unavailable in previous FBR studies. The validity of the model was confirmed through comparisons with empirical bed-expansion correlations and Hsu’s gas-temperature data, that demonstrated strong agreement and the ability of the model to capture the coupled thermal–hydrodynamic behavior of the system. In addition to the conventional observations documented in previous studies, this study identifies distinct flow-regime transitions and bed-voidage evolution that are unique to SiCl4. These findings demonstrated the impact of SiCl4’s reactive transport behavior on fluidization stability. Under bubbling conditions, the model uncovered a characteristic SiCl4 distribution pattern that more significantly enhanced gas–solid mixing in comparison to previous report. Additionally, it predicts rapid heat equilibration within ~10 mm of bed height - a behavior not documented in earlier hydrochlorination studies. Chemically, the model predicted a maximum SiHCl3 concentration of 13.08% and an SiCl4 conversion of 28.97%, thereby offering new mechanistic insight into how fluidization dynamics directly govern reaction performance. Overall, this work provides the first specialized CFD framework for SiCl4 hydrochlorination, thus establishing a novel mechanistic understanding of its fluidization–reaction coupling. Furthermore, it offers a more accurate predictive basis for optimizing industrial FBR systems employed in silicon-based chemical manufacturing.